2013
DOI: 10.7763/ijiet.2013.v3.233
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Students’ Acceptance of e-Learning Environments in Developing Countries:A Structural Equation Modeling Approach

Abstract: A quantitative methodology approach was adopted in this study. To test the hypothesized research model, data were collected from 569 undergraduate and postgraduate students studying in Lebanon via questionnaire. The collected data were analysed using structural equation modeling (SEM) technique based on AMOS methods and in conjunction with multi-group analysis. As hypothesized, the results of the study revealed perceived usefulness (PU), perceived ease of use (PEU), social norms (SN) and Quality of Work life (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
120
3
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 128 publications
(148 citation statements)
references
References 30 publications
18
120
3
7
Order By: Relevance
“…There is considerable evidence of the significant effect of BI on AU in information technology acceptance studies (e.g. Venkatesh et al, 2003Venkatesh et al, , 2012Venkatesh and Zhang, 2010;Tarhini et al, 2013b). This has recently been extended to the IB context (Im et al, 2011;Ma et al, 2010;Yu, 2012).…”
Section: Bi and Actual Usagementioning
confidence: 99%
“…There is considerable evidence of the significant effect of BI on AU in information technology acceptance studies (e.g. Venkatesh et al, 2003Venkatesh et al, , 2012Venkatesh and Zhang, 2010;Tarhini et al, 2013b). This has recently been extended to the IB context (Im et al, 2011;Ma et al, 2010;Yu, 2012).…”
Section: Bi and Actual Usagementioning
confidence: 99%
“…The benefits of this program were highlighted in enhancing employees' value, evoking employees' learning skills, enhancing hands-on experiences, and increasing job satisfaction. Tarhini et al (2013a) empirically validated an extended Technology Acceptance Model (TAM) to include social norms and quality of work life constructs in the Lebanese context. The researchers collected data from 569 undergraduate and postgraduate students studying in Lebanon via questionnaire, and performed structural equation modeling technique based on AMOS methods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, blended learning (combined, hybrid, integrative) is achieving the learning objectives through the applications of specific technologies in order to customize the act of learning and to transfer knowledge and skills to the right person at the right time. In addition, Tarhini et al (2013a) examined different Web 2.0 technologies and web-enabled learning platforms to generate technology-rich learning environments such as exploiting the blended learning technologies and applications. Furthermore, they found such technologies are digital, making them highly adaptable and integrative; globally ubiquitous, making them accessible to anyone and anywhere since an internet connection exists; low cost or free, making them accessible to anyone with a computer or mobile device; and could be used in an academic setting.…”
Section: Introductionmentioning
confidence: 99%
“…The success in the implementation of electronic learning (e-learning) systems and its tools is directly related to the users' understanding, and their knowledge and skills to understand and use computers and cyberspace. Many studies showed that these factors affected people's willingness to accept educational technology and their behavior to use web-based learning (2). Elearning, as a new approach in distance education includes education through electronic media, internet, intranet, extranet, audio and videotapes, satellite broadcasts, television, and compact disks (CDs).…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, the quality of the education system as a function of the whole educational system was intended to be measured by the perception of students. Tarhini et al (2) noted that: "the role of technology is to make it possible for the business processes to improve and speed up students' work processes, including providing communication with their teachers or other students". In e-learning, system quality refers to the network speed and quality of the learning management system (LMS) capabilities to meet the needs of students in receiving educational content, and communicating with the teacher and other students.…”
Section: Introductionmentioning
confidence: 99%